1990
DOI: 10.1002/1097-0142(19900915)66:6<1213::aid-cncr2820660622>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Frequent occurrence of cytogenetic abnormalities in sporadic nonmedullary thyroid carcinoma

Abstract: Cytogenetic studies may provide important clues to the molecular pathogenesis of thyroid neoplasia. Thus, the authors attempted cytogenetic studies on 12 thyroid carcinomas: seven papillary, three follicular, and two anaplastic. Successful cytogenetic results were obtained on all 12 tumors; nine (75%) had one or more chromosomally abnormal clones. Four of the papillary carcinomas had a simple clonal karyotype, and three had no apparent chromosome abnormality. All four abnormal papillary tumors contained an ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
38
4

Year Published

1992
1992
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(49 citation statements)
references
References 23 publications
7
38
4
Order By: Relevance
“…We used four markers at chromosome 3p25-14. LOH was found in 20% of the tumors, but only a single tumor showed LOH at this location and not on chromosome lOq, which is in contrast to earlier reports (Jenkins et al 1990;Herrmann et al 1991;Roque et al 1993). Although small interstitial deletions cannot be excluded, we conclude that LOH on 3p is probably not a prerequisite for development of follicular thyroid carcinomas.…”
Section: Discussioncontrasting
confidence: 85%
“…We used four markers at chromosome 3p25-14. LOH was found in 20% of the tumors, but only a single tumor showed LOH at this location and not on chromosome lOq, which is in contrast to earlier reports (Jenkins et al 1990;Herrmann et al 1991;Roque et al 1993). Although small interstitial deletions cannot be excluded, we conclude that LOH on 3p is probably not a prerequisite for development of follicular thyroid carcinomas.…”
Section: Discussioncontrasting
confidence: 85%
“…This patient also had nesidioblastosis, a supposedly paraneoplastic disorder of endocrine pancreatic cells that proliferate reactively in close contact with and complicating disease processes of the exocrine pancreas, e.g., pancreatic carcinomas (Eusebi et al, 1981;Kloppel & Heintz, 1984;Permert et al, 1991). Rearrangements of lOq have previously been found in, e.g., thyroid tumours -the only endocrine neoplasms that have been cytogenetically examined in any numbers -and it has been suggested that they characterize nonmedullary carcinomas, especially those whose growth pattern is papillary (Jenkins et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…1-6) is located on human chromosome 10q21, where potential tumor suppressor genes (TSGs) have been hypothesized to exist for prostate and other cancers (5,(7)(8)(9)(10)(11)(12)(13)(14)(15). However, the specific relevance of the ANX7 gene for cancer only became apparent after we created a knockout for this gene in the mouse (16).…”
mentioning
confidence: 99%